Child development - Salkind, Neil J. (Macmillan psychology reference series, 2002)
Covers human development from conception through adolescence, summarizing the latest research on physical, cognitive, social and emotional development and behavior, including areas of law, medicine, psychiatry, and demography among others. Contains black-and-white photos, and charts. Appendices contain lists of pertinent organizations and agencies and tables of statistical data. Volume 1 of the Macmillan Psychology Reference series.